Effect of vanadium content in coatings on their catalyticactivity in the hydrogen evolution reaction - Sakhnenko, M. D.; Zhelavska, Yu. A.; Proskurina, V. O.; Korohodska, A. M. (Vasyl’ Stus Donetsk National University, 2025)
Аnalysis based on the literature data allows us to predict the catalytic activity of the HER for materials containing vanadium.
Keywords: electrochemical hydrogen production; hydrogen; vanadium; cobalt-vanadium alloy; electrolysis